Subcutaneous Transplantation of Neural Precursor Cells in Experimental Autoimmune Encephalomyelitis Reduces Chemotactic Signals in the Central Nervous System. (28th October 2015) - Ravanidis, Stylianos; Poulatsidou, Kyriaki Nepheli; Lagoudaki, Roza; Touloumi, Olga; Polyzoidou, Elena; Lourbopoulos, Athanasios; Nousiopoulou, Evangelia; Theotokis, Paschalis; Kesidou, Evangelia; Tsalikakis, Dimitrios; Karacostas, Dimitrios; Grigoriou, Maria; et al.
Abstract : The effects of neural precursor cell (NPC) transplantation on the clinical course and the pathological features of experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis, were studied in mice. NPC recipients exhibited improved clinical outcome and less pronounced pathological features in their spinal cord. NPCs ameliorated EAE potentially by modulating the levels of chemokines expressed in the inflamed CNS, thus resulting in the impaired recruitment of immune cells. Abstract: : Neural precursor cell (NPC) transplantation has been proposed as a therapy for multiple sclerosis (MS) and other degenerative disorders of the central nervous system (CNS). NPCs are suggested to exert immune modulation when they are transplanted in the animal model of MS, experimental autoimmune encephalomyelitis (EAE). Herein, we explore whether the effect of NPC transplantation on the clinical course and the pathological features of EAE is combined with the modulation of chemokines levels expressed in the inflamed CNS. NPCs were isolated from brains of neonatal C57/Bl6 mice and were subcutaneously administered in female mice with myelin oligodendrocyte glycoprotein (MOG)-induced EAE. Clinical signs of the disease and transcript analysis of the CNS in the acute phase were performed. In addition, the presence of inflammatory components in the spinal cord was evaluated and ex vivo proliferation of lymphocytes was measured. NPC recipients exhibited ameliorated clinical outcome and less pronounced pathological features in their spinal cord. Downregulation of chemokine mRNA levels throughout the CNS was correlated with diminished Mac-3-, CD3-, and CD4-positive cells and reduced expression levels of antigen-presenting molecules in the spinal cord. Moreover, NPC transplantation resulted in lymphocyte-related, although not splenocyte-related, peripheral immunosuppression. We conclude that NPCs ameliorated EAE potentially by modulating the levels of chemokines expressed in the inflamed CNS, thus resulting in the impaired recruitment of immune cells. These findings further contribute to the better understanding of NPCs' immunomodulatory properties in neuroinflammatory disorders, and may lead to faster translation into potential clinical use. Significance: Endogenous neural precursor cells of the central nervous system are able to migrate and differentiate toward mature cells to repair an injury. There is increasing evidence that autologous transplantation of these cells in experimental autoimmune encephalomyelitis, the animal model of multiple sclerosis, may have a beneficial effect on the disease process. Several mechanisms have been proposed—among them, the potentiation of endogenous precursor cell differentiation of the central nervous system and the modulation of demyelinating and neurodegenerative immune-mediated processes. This article provides evidence of interference in immune signaling within the central nervous system as a potential mechanism underlying the immunomodulatory properties of transplanted neural precursor cells.